2014
DOI: 10.1177/0093854814521415
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Antisocial Values and Attitudes in Justice-Involved Male Youth

Abstract: The Risk–Need–Responsivity (RNR) framework for working with offenders has been well validated. Factors that contribute to reoffending within adult and youth forensic populations have been identified, including antisocial attitudes, but less is known about the measurement of this construct in youth. Thus, in the present study, the reliability and validity of criminal attitudes measures were examined in a sample of justice-involved male youth (N = 291). Two measures widely used with adult offenders were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…Decades of research have found a huge number of factors significant to the origins and maintenance of delinquent behaviour (Skilling & Sorge, 2014), such as antisocial peers or attitudes, personality or misconduct problems, poor parent-child relations, educational difficulties and/or ineffective use of leisure time are the best predictors of delinquency (Campbell, Schmidt, & Wershler, 2016;Cauffman & Steinberg, 2012;Contreras, Molina, & Cano, 2011;Grieger & Hosser, 2014;Heilbrun et al, 2000;Simourd & Andrews, 1994). The domain of behavioural history is the strongest predictor of future delinquency (Casey, 2011;Cottle, Lee, & Heilbrun, 2001;Farrington, 2005;Frick, 2012;Frick, Ray, Thornton, & Kahn, 2014;Wasserman et al, 2003) meaning that the earlier the onset of behaviour problems, the worse predictions of desistance from antisocial behaviour are in the future (Dishion & Patterson, 2006;Loeber & Farrington, 2000;Moffitt, 1993Moffitt, , 2006.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Decades of research have found a huge number of factors significant to the origins and maintenance of delinquent behaviour (Skilling & Sorge, 2014), such as antisocial peers or attitudes, personality or misconduct problems, poor parent-child relations, educational difficulties and/or ineffective use of leisure time are the best predictors of delinquency (Campbell, Schmidt, & Wershler, 2016;Cauffman & Steinberg, 2012;Contreras, Molina, & Cano, 2011;Grieger & Hosser, 2014;Heilbrun et al, 2000;Simourd & Andrews, 1994). The domain of behavioural history is the strongest predictor of future delinquency (Casey, 2011;Cottle, Lee, & Heilbrun, 2001;Farrington, 2005;Frick, 2012;Frick, Ray, Thornton, & Kahn, 2014;Wasserman et al, 2003) meaning that the earlier the onset of behaviour problems, the worse predictions of desistance from antisocial behaviour are in the future (Dishion & Patterson, 2006;Loeber & Farrington, 2000;Moffitt, 1993Moffitt, , 2006.…”
mentioning
confidence: 99%
“…Individual characteristics play an important role in manifestation of delinquent behaviour (Andrews & Bonta, 2010;Skilling & Sorge, 2014). Antisocial personality pattern refers to extremes of normal dimensions of personality that exist within general population (Grieger & Hosser, 2014;Hare & Neumann, 2010); however, there are some doubts whether any particular type of personality can be labelled for adolescents as there is a threat that some maladaptive features prevailing in adolescence can lead to the positive false assessment of antisocial personality (Hart, Watt, & Vincent, 2002;Seagrave & Grisso, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found moderate correlations between PIDS scores and rearrests (r = .32) as well as reincarcerations (r = .31) in nonviolent male adult offenders (Simourd & Van De Ven, 1999). Although these results show the utility of the scale in assessing these kinds of attitudes, little to no work has been done with the PIDS for assessing attitudes in females specifically, although its predictive validity has been recently demonstrated with adolescent male offenders (Skilling & Sorge, 2014).…”
Section: Criminal Attitudes: Measurement Validation and Gender Diffmentioning
confidence: 77%
“…correlated with recidivism (r = .36) in a sample of adolescent male offenders(Skilling & Sorge, 2014). Cronbach's alphas with the present adolescent sample are acceptable, with α = .85 for males and α = .87 for females.Youth-Level of Service Inventory (YLS-CMI, 2.0; Hoge & Andrews, 2011).…”
mentioning
confidence: 99%